2014
DOI: 10.1210/jc.2014-2563
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of GWASs, Human Protein Interaction, and Gene Expression Identified Gene Modules Associated With BMDs

Abstract: Context:To date, few systems genetics studies in the bone field have been performed. We designed our study from a systems-level perspective by integrating genome-wide association studies (GWASs), human protein-protein interaction (PPI) network, and gene expression to identify gene modules contributing to osteoporosis risk. Methods:First we searched for modules significantly enriched with bone mineral density (BMD)-associated genes in human PPI network by using 2 large meta-analysis GWAS datasets through a dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The systems genetics approach for BMD has been applied in recent studies by integrating genomic data and coexpression networks of other genomics data. (15)(16)(17) Farber and colleagues carried out the first two systems-level studies for BMD based on monocyte transcriptional gene expression network with a relatively small sample size. He and colleagues performed a system analysis on BMD by integrating GWAS data and known human protein interactions.…”
Section: Journal Of Bone and Mineral Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…The systems genetics approach for BMD has been applied in recent studies by integrating genomic data and coexpression networks of other genomics data. (15)(16)(17) Farber and colleagues carried out the first two systems-level studies for BMD based on monocyte transcriptional gene expression network with a relatively small sample size. He and colleagues performed a system analysis on BMD by integrating GWAS data and known human protein interactions.…”
Section: Journal Of Bone and Mineral Researchmentioning
confidence: 99%
“…Both studies integrated GWAS data with weighted gene coexpression network analysis (WGCNA) and set up a good example of identification of functional connections between genes through disease‐relevant microarray gene expression data. Another network‐assisted study for BMD was reported by He and colleagues by using GWAS data, gene expression data, and human protein‐protein interaction data . Their work highlighted two modules and genes in those modules associated with BMD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the evaluation of module content and topology, they identified a number of novel candidate genes/subnetworks for osteoporosis susceptibility and revealed functional connections between novel genes with evidence of association and those with a previously established role in the regulation of bone metabolism [109]. We also conducted a study, integrating GWASs, human protein-protein interaction (PPI) network, and gene expression from high versus low BMD subjects, and found two modules of genes contributing to osteoporosis risk [111]. The two modules were enriched with BMD-associated genes in human PPI network and were identified significantly in the GWASs for BMD.…”
Section: Using Pbms As a Working Cell Model To Study For Bone Diseasesmentioning
confidence: 99%
“…Recently, our group [9] and Farber [10] independently illustrated that PBM transcriptomic data can be used to extract additional biological functional information from GWAS datasets, allowing for discovery of novel osteoporosis-associated genes and prioritization of genes and SNPs for replication studies. Our group also conducted another in silico study, integrating GWASs, human protein-protein interaction (PPI) network, and monocytic gene expression from high vs. low BMD subjects, and found two modules of genes contributing to osteoporosis risk by participating in Wnt receptor signaling and osteoblast differentiation, respectively [11]. Together, these studies indicate that PBMs represent a valuable working cell model for studying mechanistic differences occurring in bone metabolism between health and disease conditions.…”
Section: Introductionmentioning
confidence: 99%